Expedient - Fernando de Assis Rodrigues (Revista Eletrônica Competências Digitais para Agricultura Familiar, 2017)
Expedient (English) Electronic Journal Digital Skills for Family Farming (RECoDAF) ISSN (electronic) – 2448-0452 Expedient of Volume 3, Issue 2, July – December of year 2017 EDITORIAL BOARD Head Editor Fernando de Assis Rodrigues – São Paulo State University (UNESP) Editorial Board Fernando de Assis Rodrigues – São Paulo State University (UNESP) Ricardo César Gonçalves Sant’Ana – São Paulo State University (UNESP) Executive Comission Diana Vilas Boas Souto Aleixo – Londrina State Univerisity (UEL) Fábio Mosso Moreira – São Paulo State University (UNESP) Pedro Henrique Santos Bisi – São Paulo State University (UNESP) Jacquelin Teresa Camperos Reyes – São Paulo State University (UNESP) Ad hoc peer reviewers of this issue Ana Elisa Lourenzani – São Paulo State University (UNESP) Carolina Martins Fernandes – São Paulo State Technological College (FATEC) Cristiane Hengler Correa Bernardo – São Paulo State University (UNESP) Diana Vilas Boas Souto Aleixo – Universidade Estadual de Londrina (UEL) Elaine Parra Affonso – São Paulo State Technological College (FATEC) Elvio Gilberto da Silva – Universidade do Sagrado Coração (USC) Fábio Mosso Moreira – São Paulo State University (UNESP) Marina Funichello – São Paulo State Technological College (FATEC) Bibliographic Standards Normalization Elizabete Cristina de Souza Aguiar Monteiro – São Paulo State University (UNESP) Graphical Art Leonardo Felipe Franchi – University of São Paulo (USP)